Motors vs. operators in simulated root canal shaping - Kevin Hofpeter; Matthias Zehnder; Shengjile Deari (Frontiers in Dental Medicine)
IntroductionThe impact of contemporary endodontic motors on shaping outcomes has not been weighed against that of the motor operators.Materials and methodsOne motor (X-Smart Pro+) specifically developed for the reciprocating files that were used (Reciproc Blue R25) was compared to three cordless counterparts, two of which lacked a designated reciprocation mode. Standardized J-shaped canals in bovine incisor roots were instrumented by four different operators, who were residents with similar levels of education and clinical experience. One reciprocating file per simulated root canal was used. The root canal models were pre-warmed and kept in a vice at 37°C in a water bath. The operators were instructed to instrument two simulated canals per motor in a random sequence, applying three pecking motions and alternating with 3% NaOCl irrigation. Instrumentation time was measured. Pre- and postoperative images obtained using a digital microscope were superimposed to assess canal transportation. Parametric tests (two-way ANOVA) were applied to weigh the overall effects of the motor and operator on instrumentation time and canal transportation. The impact of the motor and operator on the number of unwound flutes was explored using likelihood ratio tests. The level of significance was set at 5% (P < 0.05).ResultsOperators had a highly significant (P < 0.001) impact on instrumentation time and file unwinding, while motors did not (P > 0.05). File unwinding was negatively correlated with instrumentation time (P < 0.001). There was no effect of either the motor or the operator on canal transportation (P > 0.05).ConclusionTechnological advancements in endodontic motors do not necessarily compensate for operator variability.